Psychophysiological reactions analysis at stress-testing of the military universities cadets - D. I. Tishakin; O. A. Jafarova; O. L. Grebneva (Бюллетень сибирской медицины, 2010)
The purpose of this study — to explore psychophysiological mechanisms to respond in a stressful situation. We used the methods of psycho-diagnostics, and specially designed protocols psychophysiological testing. The study was conducted on a group of cadets of the military university, candidates for the combined team on the tactical and technical decathlon. The study identified prognostic group of successful and unsuccessful athletes and describes the characteristic for each group of physiological patterns.